2023
DOI: 10.3390/v15020372
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Temporal Dynamics of Natural Recombination in Noroviruses

Abstract: Noroviruses infect a wide range of mammals and are the major cause of gastroenteritis in humans. Recombination at the junction of ORF1 encoding nonstructural proteins and ORF2 encoding major capsid protein VP1 is a well-known feature of noroviruses. Using all available complete norovirus sequences, we systematically analyzed patterns of natural recombination in the genus Norovirus both throughout the genome and across the genogroups. Recombination events between nonstructural (ORF1) and structural genomic regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…In picornaviruses, there was frequent recombination within the nonstructural genome region with no prominent hotspots and almost absent recombination within the structural genome region. Caliciviruses routinely exchanged full structural and nonstructural blocks of the genome, but had few, if any, recombination events within these regions [ 73 ]. In astroviruses, moderate recombination was observed within both structural and nonstructural genomic regions.…”
Section: Scientific Programmentioning
confidence: 99%
“…In picornaviruses, there was frequent recombination within the nonstructural genome region with no prominent hotspots and almost absent recombination within the structural genome region. Caliciviruses routinely exchanged full structural and nonstructural blocks of the genome, but had few, if any, recombination events within these regions [ 73 ]. In astroviruses, moderate recombination was observed within both structural and nonstructural genomic regions.…”
Section: Scientific Programmentioning
confidence: 99%
“…The ORF-1 encodes six non-structural proteins including the RNA-dependent RNA polymerase (RdRp), whereas ORF-2 and ORF-3 encode the major capsid protein (VP1) and minor capsid protein, respectively [ 6 ]. Genetic recombination and mutation are responsible for the existing diversity of NoVs [ 7 ]. Based on the variations on the VP1 region, NoVs are classified into 10 genogroups (GI-GX) and 49 genotypes, with genogroups I and II being frequent causes of infection in humans and NoV GIV rarely [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the GI, GII, GIV, GVIII and GIX groups can infect humans and cause AGE, with GI and GII are the most predominant genogroups associated with AGE in humans. Recently, a large number of studies have shown that NoV recombination often occurs near or within the ORF1 (RdRp)/ORF2 (VP1) junction, leading to the emergence of various recombinant strains worldwide ( Kendra et al., 2022 ; Zheng et al., 2022 ; Vakulenko et al., 2023 ). For example, the recombinant NoV GII.2[P16] associated with AGE emerged in 2016–2017 and spread across Europe and many countries in Asia ( Lu et al., 2017 ; Parra, 2019 ; Wang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%